Visible light driven (Fe, Cr)-codoped La2Ti2O7 photocatalyst for efficient photocatalytic hydrogen production - Hu, S.; Jia, Lichao; Chi, B.; Pu, J.; Li, J. (Elsevier SA, 2014)
Highly visible-light response (Fe, Cr)-codoped La2Ti2O7 photocatalysts are synthesized by sol–gel process. The crystal phase, morphology and optical absorption activity of the samples are characterized by X-ray diffraction, scanning electron microscope, X-ray photoelectron spectroscopy, and UV–vis diffuse reflectance spectra. The results reveal that the calcination temperature and dopant concentration have strong influence on the phase structures, crystallinity and morphology. The UV–vis diffuse reflectance spectra indicate that Fe and Cr ions codoping can extend optical absorption to the visible-light region and narrow the band gap obviously. The photocatalytic hydrogen and oxygen production activities are evaluated in CH3OH and AgNO3 aqueous solution under solar light irradiation. NiOx (0.5 wt%) loaded (Fe, Cr)-0.005-LTO-1150 shows the best photocatalytic H2 production activity with the productivity of 360.203 μmol g−1 h−1 and the apparent quantum efficiency of 2.44%, which suggests that the synergistic effect of Fe and Cr codoping is favorable to enhance the photocatalytic efficiency. The photocurrent of (Fe, Cr)-codoped La2Ti2O7 is more than two times of that for Fe-doped La2Ti2O7 photocatalyst. The efficient photocatalytic hydrogen production and the high photocurrent of (Fe, Cr)-0.005-LTO-1150 are originated from the optimized combination of the physical–chemical properties, the small band gap and the low recombination rate of photoelectron–holes.